FRI0550 Tumor Necrosis Factor-Alpha Blockade in Recurrent and Disabling Chronic Sciatica Associated with Post-Operative Peridural Lumbar Fibrosis: Results of a Two-Year Double-Blind, Randomized, Controlled Study. (9th June 2015) - Nguyen, C.; Sanchez, K.; Palazzo, C.; Zee, N.; Feydy, A.; Quinquis, L.; Grabar, S.; Revel, M.; Lefèvre-Colau, M.-M.; Poiraudeau, S.; Rannou, F.
Abstract : Background: The prevalence of persistent or recurrent post-operative back or lower limb pain in patients who underwent discectomy or laminectomy is up to 15% and its management remains challenging. Post-operative peridural fibrosis secondary to scar formation is one of the major cause of recurrent pain symptoms in the legs after back surgery. We hypothesized that drugs targetting inflammatory-associated fibrotic processes may be of interest in this condition. Objectives: To assess the efficacy of tumor necrosis factor (TNF)-α inhibition with infliximab (IFX), as an anti-inflammatory and anti-fibrotic agent, in the treatment of post-operative peridural lumbar fibrosis-associated disabling chronic sciatica. Methods: A two-year double-blind, randomized, controlled study was conducted in a French tertiary care unit. Thirty-five patients presenting with post-operative peridural lumbar fibrosis-associated sciatica were randomized in two groups. The IFX group (N=17) was treated with a single intravenous infusion of 3 mg/kg IFX, and the placebo group (N=18) with a single saline serum infusion. The primary outcome was a 50% reduction in sciatica on visual analog scale (VAS) at day 10. Secondary outcomes were radicular and lumbar pain at day 0, 2 hours after infusion, and radicular and lumbar pain, Québec disability score, drug sparing effect, and tolerance, at days 10, 30, 90, and 180. Results: The two groups did not differ for baseline characteristics, except for radicular pain and neuropathic pain (VAS scores=55.0[50.0-70.0] in the placebo group vs 70[65.0-85.0] in the IFX group, and 45.0[41.0-73.0] vs 62.5[40.0-75.0], respectively). At day 10, no significant difference was found between placebo and IFX groups for the primary outcome (50% reduction in sciatica was observed in 3[17.6%] patients vs 5[27.8%], p=0.69, respectively). The frequency of patients reaching the Patient Acceptable Symptom State for radicular pain was significantly higher in the placebo than in the IFX group, 2 hours after infusion (12[70.6%] vs 5[27.8%], p=0.01, respectively). The two groups were comparable for all other secondary outcome measures. Conclusions: Treatment with a single 3 mg/kg IFX infusion for recurrent sciatica pain associated with post-operative peridural lumbar fibrosis does not significantly reduce radicular symptoms at day 10. Disclosure of Interest: None declared